Enhancement of activation-induced T cell proliferation by SIRPG in a CD47-independent manner - Marguerie, Flavien; Saifi, Mohammad A.; Geary, Benjamin; Barnes, David; Lim, Laura; Jonsson, Anna Helena; Ho, I-Cheng (Frontiers in Immunology, 2025)
SIRPG, a primate-specific type 1 transmembrane protein in the Signal Regulatory Protein (SIRP) family, is predominantly expressed in T cells. It contains a short cytoplasmic domain, which does not contain any known signaling motif, and its only known ligand is CD47. Several genetic variations in SIRPG, including the V263A (rs6043409) polymorphism, linked to increased type 1 diabetes risk, highlight its potential importance. However, its expression and physiological role remain largely unclear due to its absence in rodents. Here, we demonstrate that SIRPG and GzmB exhibit near mutually exclusive expression in resting peripheral CD8+ T cells. We further show that SIRPG serves as a valuable marker for GzmK-expressing CD8+ T cells in peripheral blood and that its expression in both CD4+ and CD8+ T cells is upregulated by anti-CD3 stimulation, with further enhancement by the TNFα inhibitor adalimumab, but not certolizumab. While SIRPG ablation minimally affects T cell activation and IFNγ/TNFα production, it impairs the expression of mitosis-regulating genes like UBE2C and TOP2A, leading to reduced proliferation, and alters the expression of certain activation-induced surface molecules, including CRTAM. Notably, SIRPG-mediated proliferation and CRTAM expression are cell-autonomous and CD47-independent. Structural and functional analyses reveal that SIRPG-driven proliferation is independent of its extracellular D1 domain, not significantly affected by the V263 variant, but dependent on its cytoplasmic domain. Collectively, our findings offer novel insights into the expression, function, and mechanism of action of SIRPG in T cells.